Contribuições gravitacionais efetivas para o tensor de polarização da eletrodinâmica escalar - Jean Carlos Coelho Felipe (2010)
This work, describe the interaction of scalar electrodynamics with gravitation by way of effective field theory. Particularly, we check if there is any gravitational contribution for polarization's tensor for scalar electrodynamics the order of 1 loop, and if this contribution is gauge dependent. To implement the calculations we use the ImplicitRegularization method (RI). This method is independent of how the divergent integrals are regularized. The main motivation to realize this calculation stems from the fact that recently some studies have shown that gravitational contributions for coupling of theory of gravitation with Yang-Mills theory are gauge dependent [1, 2, 3, 4]. We show the existence of a gravitational contribution for scalar electrodynamics coupling the gravitation wich is gauge dependent. Particularly this dependence appears in a effective contribution of the model.